In Vivo Models to Evaluate Antitumor Drugs Effect on Vasculogenic Mimicry - Fonseca-Alves, Carlos E. [UNESP]; Lainetti, Patrícia de F. [UNESP] (Springer Nature, 2022)
The vasculogenic mimicry (VM) in vivo evaluation is challenging, and new models have been proposed to evaluate antitumor effect of different compounds using in vivo models. However, there is no gold standard in vivo models established for VM evaluation. As occurs for other in vivo tumor analysis, the use of immunodeficient mouse model and cell line with in vivo tumorigenicity and ability to induce vasculogenic mimicry is the most used model.
Keywords: Anticancer compounds; Cancer cell; Vascular-like channels; Vasculogenic; Xenograft model